White spot lesions in patients with orthodontic treatment. Literature review. - Sanchez-Tito, Marco Antonio (2021)
White spot lesions are common side effects in patients with orthodontic treatment. They are the product of the attack of organic acids capable of disorganizing the structure of the enamel and its formation is associated with the presence of risk factors such as prolonged orthodontic treatment time, poor oral hygiene and early treatment initiation ages. In the literature there are various diagnostic methods for this type of lesions, as well as various proposals for prevention and/or treatment. The aim of this literature review is to present the scientific evidence related to the formation of white spot lesions, their prevalence, risk factors associated with their formation, and to describe the most frequent diagnostic methods and mechanisms of prevention and treatment.